PERUMUSAN KONSEP STRATEGI PENINGKATAN SENTRA INDUSTRI OLEH-OLEH DAN SOUVENIR SEBAGAI DESTINASI WISATA BARU DI DAERAH ISTIMEWA YOGYAKARTA - Niken Widyastuti; Medi Trilaksono Dwi Abadi; Andi Purnawan Putra (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The concept of the center as one of the tourism business potentials referred to here will be able to increase competitiveness and create national industrial strength in the form of interrelation, dependence, and mutual support between the upstream industry, downstream industry, supporting industry, and related industries, which means it can also reduce the dependence of the manufacturing industry on imports of capital goods, intermediary inputs, raw materials and other components. In line with this, it is deemed necessary to map the destination centers for souvenirs and souvenirs for the development of small, micro, and medium enterprises that are formed in a location as a new destination center in Yogyakarta, in addition to increasing economic growth and equitable regional economic development. The purpose of this study is to identify leading industrial centers from souvenir and souvenir centers to be developed into new destinations in DI Yogyakarta, (2). Analyzing the strategy of developing a gift and souvenir center by considering the aspects of strengths, weaknesses, opportunities and threats. The research method used is descriptive qualitative. The results showed that: (1). The souvenir and souvenir centers in each district/city of DIYogyakarta already have sufficient potential to be developed into new tourist destinations based on the fact that the souvenir and souvenir centers have met the five destination criteria. tourism, namely visitors or tourists can be part of the development of the destination itself, there is an authentic experience felt by tourists who come directly to the center, there is participatory, interactive, and informal learning, and is closely related to the local community, (2). The souvenir and souvenir industry center has a dominant and strongly attached character or product theme as a component of the area's imaging (typical), (3). The availability and conditions of accessibility that are closest to tourist attractions and other amenities (roads, home stays, etc.).